Errors in Otolaryngology Revisited. (5th February 2014) - Shah, Rahul K.; Boss, Emily F.; Brereton, Jean; Roberson, David W.
Abstract : Objective: A decade ago, a survey study identified areas of risk and proposed a classification schema for otolaryngology errors. The objective of the present study is to obtain current data for comparison using a similar methodology. Study Design: Survey study. Setting: An anonymous online survey was distributed via the American Academy of Otolaryngology—Head and Neck Surgery (AAO‐HNS) weekly email. Subjects and Methods: Members of the AAO‐HNS were asked to describe any event in their practice that they felt should not have happened. Events were classified using the prior schema with minor modifications. Results: Of 681 respondents, 445 (66%) reported an event within the past 6 months, from which 222 reports were extracted. The mean age of the affected patients was 41 ± 24 years. An adverse consequence occurred in more than half of events, with corrective action taken in 82.8%. Of the respondents, 68% subsequently changed their practice patterns. The domains with the most reported errors were technical (27.9% of all events, 71% with major morbidity), administrative (12.2%, 3.7%), diagnostic testing (10.8%, 8.3%), and surgical planning (9.9%, 45.5%). There were 8 wrong‐site surgeries, 23 cranial nerve injuries (91.3% major morbidity), and 9 errors during endoscopic sinus surgery (55.6% major morbidity). There were 4 deaths. Conclusion: There has been disappointingly little overall change. Otolaryngologists remain vulnerable to errors and related adverse events. The domains with the greatest risk for error‐related major morbidity have changed little and include errors in technical, administrative, diagnostic testing, surgical planning, and surgical equipment. Awareness of high‐risk areas may help to focus preventive efforts in these domains.